APPLICATION OF LEAN SIX SIGMA METHODOLOGY ON CONSTRUCTION FIELD – PART 1: DEFINE PHASE - Attia, Walid A. Attia; El-Taweel, Ahmed A. (Acta Scientiae et Intellectus, 2024)
This aim of this study was to apply Lean Six Sigma methodology through the famous DMAIC (Define, Measure, Analyze, Improve and Control) approach to improve the efficiency of construction activities. Lean manufacturing concept is based on increasing the efficiency by eliminating non-added value (waste) activities. Six Sigma is a statistically-based process improvement methodology that aims to reduce defects to a rate of 3.4 defects per million defect opportunities. Lean (with its roots in the Toyota Production System) and Six Sigma (with its roots in the Motorola Quality System) is essentially the combination of two strategies, cultures, methodologies and tool sets with overlapping themes but are also uniquely different value propositions. Six Sigma is limited to process quality tools and does not have the process speed tools. Similarly, Lean does not possess the tools to bring a process under statistical control, nor does it define a sustaining infrastructure or emphasize customer focus as does Six Sigma. Thus, achieving the goals of enterprise requires both Lean and Six Sigma.